PENGELOLAAN WILAYAH LATIHAN TARUNA DI DESA JOGOMULYO KECAMATAN TEMPURAN KABUPATEN MAGELANG UNTUK MENDUKUNG PERTAHANAN - Titiek Herawati; Dwi Joko Siswanto; M. Sigit Saksono; Untung Widagdo; Marjitulastri; Sermatutar Felik Leandro; Sermatutar Muhamad Andre Nuralam R (PPM Sdirjianbang Akademi Militer, 2024)
This research is motivated by the mandate of the TNI Law No. 34 of 2004 which has been implemented by the Military Academy to take a positive role and contribute to building the life of the nation and state through the management of the training area of Cadets/cadets of the Military Academy. The purpose of this study is to determine the action program of manunggal Military Academy and the community and what factors are driving and inhibiting it in supporting defense in Jogomulyo Village, Tempuran District, Magelang regency. The research methods used are qualitative methods with primary informants coming directly from the head of Akmil and staff, village communities, community leaders, village officials, Babinsa and Babinkamtibmas. From the results of research conducted, it was concluded that the action of the Military Academy unity with the community in the Jogomulyo Village training area was carried out through various activities, namely Karya bakti, Prodi community service and social service. The main key driving factor in the success of the program to support defense is the commitment of the entire leadership of the Military Academy to always establish unity with the community through various empowerment to improve the welfare of the community in the Cadet Training Area. The main inhibiting factor is that until now there is still the impression that the Akmil activities carried out are only temporary so that the village government and the community are less convinced that the activities of aksi manunggal Akademi Militer can help improve welfare, although field data show a large public response and enthusiasm for this activity